Quantum dot composition, method of preparing the same, cured product thereof, and display device including the same

The quantum dot composition, optimized with specific monomers, oligomers, and ligands, achieves high viscosity and excellent ink jetting properties, addressing the limitations of existing compositions and enhancing the performance of quantum dot-based display devices.

JP2025063864AActive Publication Date: 2025-04-16SAMSUNG ELECTRONICS CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024173226
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-04
Filing Date
2024-10-02
Publication Date
2025-04-16
Estimated Expiration
2044-10-02

AI Technical Summary

Technical Problem

Existing quantum dot compositions for inkjet printing have difficulty achieving high viscosity suitable for electrohydrodynamic (EHD) inkjet methods, which limits their application in achieving excellent optical and ink jetting properties.

Method used

A quantum dot composition is developed that includes quantum dots, photopolymerizable monomers, oligomers with carbon-carbon double bonds and thiol groups, and a specific ligand system, achieving a viscosity of 5000 cps or less, preferably between 100 to 1000 cps, and excellent ink jetting properties.

Benefits of technology

The composition exhibits excellent optical properties, high viscosity suitable for EHD inkjet methods, and superior ink jetting performance, resulting in enhanced light emission and display device performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063864000001
    Figure 2025063864000001
  • Figure 2025063864000002
    Figure 2025063864000002
  • Figure 2025063864000003
    Figure 2025063864000003
Patent Text Reader

Abstract

To provide a quantum dot composition, a method of preparing the same, a cured product thereof, and a display device including the same.SOLUTION: The disclosure relates to a quantum dot composition, a method of preparing the same, a cured product thereof, and a display device including the same, and more particularly, to a quantum dot composition for electrohydrodynamic inkjet printing, a method of preparing the same, a cured product thereof, and a display device including the same.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a quantum dot composition, a manufacturing method thereof, a cured product thereof, and a display device including the same, and more particularly to a quantum dot composition for electrohydrodynamic inkjet printing, a manufacturing method thereof, a cured product thereof, and a display device including the same. [Background technology]

[0002] Quantum dots (QDs) are so-called semiconductor nanocrystals, and can produce various colors by generating light of different wavelengths according to particle size without changing the type of material. They have advantages of higher color purity and light stability than existing light-emitting bodies, so they are attracting attention as a next-generation light-emitting device.

[0003] In particular, quantum dots, which have become a new trend in the display field, are dispersed in a polymer matrix and can be applied to various displays and electronic devices in the form of a complex in addition to TVs and LEDs. Quantum dots, represented by CdSe and InP, have made rapid progress in terms of luminous efficiency (quantum yield), and a synthesis method with a luminous efficiency of nearly 100% has been introduced. Based on this, TVs using quantum dot sheets are currently being commercialized. In the next stage, quantum dots are included in the color filter layer of existing LED TVs (excluding pigments and dyes), and quantum dot TVs are being developed that are self-emitting versions rather than filtering type in the color filter layer. The key to developing such quantum dot TVs is to focus on how much the luminous efficiency of quantum dots can be maintained in the process of forming pixels with quantum dots and the manufacturing process.

[0004] Meanwhile, materials for color filters are required to have high sensitivity, adhesion to substrates, chemical resistance, heat resistance, etc. Conventionally, color filters applied to displays have generally been formed through a patterning process in which a desired pattern is formed using a photosensitive resist composition through an exposure process using a photomask, and then non-exposed areas are dissolved and removed through a development process, but this has led to a problem of increased costs due to waste materials.

[0005] Recently, in order to solve the problem of increasing costs due to the high quality of materials used for pixels, methods that use materials only in desired areas and minimize the use of materials have been attracting attention, rather than the conventional patterning methods such as spin coating or slit coating. The most representative method is the inkjet method, which can be broadly classified into the bubble jet method and the piezo method. The inkjet method uses materials only in desired pixels, thereby preventing unnecessary waste of materials.

[0006] However, since the quantum dot composition used in the inkjet method is required to have a viscosity of 100 cps or less, preferably 50 cps or less, it is difficult to apply a high-viscosity ink having a viscosity exceeding 100 cps.

[0007] To overcome the drawbacks of the inkjet method, the electrohydrodynamic (EHD) inkjet method, which is capable of fine patterning, has been developed. The EHD inkjet method applies an electric potential difference between the ink ejection nozzle and the substrate, enabling fine ink printing through the electric field.

[0008] As a related prior art, Korean Patent Publication No. 10-2020-0137977 discloses a solution used in an electrohydrodynamic printing method. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Korean Patent Publication No. 10-2020-0137977 Summary of the Invention [Problem to be solved by the invention]

[0010] The problem to be solved by the present invention is to provide a quantum dot composition having a high viscosity suitable for the EHD inkjet method, excellent optical characteristics, and excellent inkjetting properties (ejection properties), and a method for producing the same.

[0011] Another object of the present invention is to provide a cured product of the quantum dot composition and a display device including the same. Effect of the Invention

[0012] The present invention provides a quantum dot composition having a high viscosity suitable for the EHD inkjet method, excellent optical characteristics, and excellent inkjetting properties (ejection properties), a method for producing the same, a cured product made from the quantum dot composition, and a display device including the same.

[0013] The quantum dot composition according to the present invention has excellent optical properties, a high viscosity suitable for the EHD inkjet method, and excellent inkjetting properties (ejection properties).

[0014] Therefore, the light emitting device and the display device including the quantum dot composition according to the present invention have excellent optical properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will now be described.

[0016] All terms (including technical and scientific terms) used in this specification may be used as commonly understood by those having ordinary knowledge in the technical field to which the present invention belongs, unless otherwise defined. Furthermore, terms defined in commonly used dictionaries are not interpreted ideally or excessively unless otherwise clearly defined.

[0017] Furthermore, throughout this specification, when a part "comprises" a certain component, this does not mean to exclude other components, but means that it may further include other components, unless specifically stated to the contrary.

[0018] In addition, in this specification, "(meth)acrylate" means acrylate and methacrylate, "(meth)acrylic" means acrylic and methacrylic, and "(meth)acryloyl" means acryloyl and methacryloyl.

[0019] In addition, in this specification, "monomer" and "monomer" have the same meaning. In the present invention, a monomer is distinguished from an oligomer and a polymer, and refers to a compound having a weight average molecular weight of 1,000 or less. In this specification, a "photopolymerizable monomer" refers to a group involved in a polymerization reaction, such as a (meth)acrylate group.

[0020] In this specification, "substitution" means that a hydrogen atom in a compound or functional group is replaced with a C1-C30 alkyl group, a C2-C30 alkenyl group, a C2-C30 alkynyl group, a C1-C30 alkoxy group, a C1-C30 heteroalkyl group, a C3-C30 heteroalkylaryl group, a C3-C30 cycloalkyl group, a C3-C15 cycloalkenyl group, a C6-C30 cycloalkynyl group, a C2-C30 heterocycloalkyl group, a halogen (-F, -Cl, -Br or -I), a hydroxy group (-OH), a nitro group (-NO 2), a cyano group (-CN), an ester group (-C(=O)OR, where R is a C1-C10 alkyl or alkenyl group), an ether group (-OR, where R is a C1-C10 alkyl or alkenyl group), a carbonyl group (-C(=O)-R, where R is a C1-C10 alkyl or alkenyl group), a carboxyl group (-COOH), and combinations thereof.

[0021] In this specification, the term "organic group" refers to a C1-C30 linear or branched alkyl group, a C2-C30 linear or branched alkenyl group, or a C2-C30 linear or branched alkynyl group, each of which may be substituted or unsubstituted.

[0022] As used herein, "alkyl" refers to a monovalent substituent derived from a straight or branched chain saturated hydrocarbon having 1 to 40 carbon atoms. Examples include, but are not limited to, methyl, ethyl, propyl, isobutyl, sec-butyl, pentyl, iso-amyl, hexyl, and the like.

[0023] As used herein, "alkenyl" refers to a monovalent substituent derived from a straight or branched unsaturated hydrocarbon having 2 to 40 carbon atoms and one or more carbon-carbon double bonds. Examples include, but are not limited to, vinyl, allyl, isopropenyl, 2-butenyl, etc.

[0024] <Quantum dot composition> A quantum dot composition according to one embodiment of the present invention includes quantum dots, photopolymerizable monomers and oligomers, where the oligomers include compounds containing carbon-carbon double bonds and compounds containing thiol groups.

[0025] The quantum dot composition according to one embodiment of the present invention is used for electrohydrodynamic inkjet printing and has a viscosity of 5000 cps or less, preferably in the range of 100 to 1000 cps, and more preferably in the range of 150 to 600 cps.

[0026] The composition of the quantum dot composition will be specifically described below.

[0027] Quantum dots

[0028] Quantum dots (QDs) are nano-sized semiconductor materials that can have different energy band gaps depending on their size and composition, and can therefore emit light of various emission wavelengths.

[0029] Such quantum dots may have a homogeneous single layer structure, a multilayer structure such as a core-shell structure, a gradient structure, or a mixture of these. In a core-shell structure, the shell may be multilayered (e.g., core / shell / shell), where each layer may comprise a different component, e.g., a (semi)metal oxide.

[0030] The quantum dots can be freely selected from II-VI group compounds, III-V group compounds, IV-VI group compounds, group IV elements, group IV compounds, and combinations thereof. When the quantum dots have a core-shell structure, the core and shell can be freely composed of the following exemplary components.

[0031] By way of example, the II-VI compound may be a binary compound selected from the group consisting of CdO, CdS, CdSe, CdTe, ZnO, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, MgSe, MgS and mixtures thereof; CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdH ternary compounds selected from the group consisting of CdZnSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, MgZnSe, MgZnS, and mixtures thereof; and quaternary compounds selected from the group consisting of CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, and mixtures thereof.

[0032] As another example, the III-V compound may be selected from the group consisting of binary compounds selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, and mixtures thereof; ternary compounds selected from the group consisting of GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, and mixtures thereof; and quaternary compounds selected from the group consisting of GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, and mixtures thereof.

[0033] As another example, the IV-VI compound may be selected from the group consisting of binary compounds selected from the group consisting of SnS, SnSe, SnTe, PbS, PbSe, PbTe, and mixtures thereof; ternary compounds selected from the group consisting of SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, and mixtures thereof; and quaternary compounds selected from the group consisting of SnPbSSe, SnPbSeTe, SnPbSTe, and mixtures thereof.

[0034] As another example, the group IV element may be selected from the group consisting of Si, Ge, and mixtures thereof. The group IV compound is a binary compound selected from the group consisting of SiC, SiGe, and mixtures thereof.

[0035] As another example, the alloy type compound is a ternary compound selected from InZnP, etc.

[0036] The two-element compound, three-element compound, or four-element compound may be present in a particle at a uniform concentration, or may be present in the same particle with a concentration distribution that is partially different. A quantum dot may also have a core / shell structure in which one quantum dot surrounds another. The interface between the core and the shell may have a concentration gradient in which the concentration of the element present in the shell decreases toward the center.

[0037] The shape of the quantum dots is not particularly limited as long as it is a shape commonly used in the art. For example, the shapes of the quantum dots may be spherical, rod-shaped, pyramidal, disk-shaped, multi-arm, or cubic nanoparticles, nanotubes, nanowires, nanofibers, nanoplate particles, and the like.

[0038] In addition, the size of the quantum dots is not particularly limited and can be appropriately adjusted within a normal range known in the art. As an example, the average particle size (D50) of the quantum dots is about 2 to 10 nm. In this way, when the particle size of the quantum dots is controlled in the range of about 2 to 10 nm, light of a desired hue can be emitted. For example, when the particle size of the quantum dot core / shell containing InP is about 5 to 6 nm, light of a wavelength of about 520 to 550 nm can be emitted, while when the particle size of the quantum dot core / shell containing InP is about 7 to 8 nm, light of a wavelength of about 620 to 640 nm can be emitted. For example, as the blue light-emitting QD, non-cadmium (Cd)-based III-V group QD (e.g., InP, InGaP, InZnP, GaN, GaAs, GaP) can be used.

[0039] In addition, the quantum dots may have a full width of half maximum (FWHM) of an emission wavelength spectrum of about 40 nm or less, and color purity and color reproducibility may be improved within this range. In addition, the light emitted through such quantum dots is emitted in all directions, and thus a wide viewing angle may be improved.

[0040] According to one embodiment of the present invention, the content of the quantum dots is 1 to 60 wt %, preferably 20 to 60 wt %, based on the total weight of the quantum dot composition depending on the properties of the quantum dots.

[0041] Oligomers In the quantum dot composition according to the present invention, the oligomer includes a compound containing a carbon-carbon double bond and a compound containing a thiol group. Preferably, the oligomer includes two or more compounds containing a carbon-carbon double bond, and may include, for example, one compound containing 2 to 3 carbon-carbon double bonds per molecule and one compound containing one carbon-carbon double bond per molecule.

[0042] In the case where the compound contains 2 to 3 carbon-carbon double bonds per molecule, the molecular weight is about 200 to 1000 g / mol, preferably about 200 to 800 g / mol, and more preferably about 200 to 500 g / mol. For example, triallyl isocyanurate can be used.

[0043] At this time, the compound containing a carbon-carbon double bond may contain one or more compounds containing a phenol group, and preferably, the compound containing a phenol group may be a compound containing one carbon-carbon double bond per molecule. After the quantum dot composition is cured, in the subsequent process, the ligands on the surface of the quantum dots are discharged in gas form (hereinafter, outgassing), which may cause problems such as cracking of the cured film, the light-emitting element, and the display device, and product defects such as poor paper lamination. However, when the composition contains one or more compounds containing a phenol group, it has the advantage of being able to reduce the generation of outgassing. For example, phenol acrylate may be used.

[0044] The compound containing a thiol group contains 2 to 4 functional groups, preferably 2 to 4 thiol groups per molecule, and more preferably 2 to 3 thiol groups per molecule. For example, glycol di(3-mercaptopropionate) can be used.

[0045] The molar ratio of the compound containing a carbon-carbon double bond to the compound containing a thiol group is 2.75:1 to 5:1, preferably 2.75:1 to 4:1, and more preferably 2.75:1 to 3.5:1.

[0046] The molar ratio of the compound containing 2 to 3 carbon-carbon double bonds per molecule to the compound containing one carbon-carbon double bond per molecule is 0.01:1 to 1.5:1, preferably 0.1:1 to 1.5:1, and more preferably 0.3:1 to 1.2:1.

[0047] In compounds containing carbon-carbon double bonds, the carbon-carbon double bonds are independently one or more selected from the group including, but not limited to, an allyl group, a vinyl group, a (meth)acrylic group, an isopropenyl group, and a 2-butenyl group.

[0048] According to one embodiment of the present invention, the content of the oligomer is 1 to 50 wt %, preferably 10 to 45 wt %, and more preferably 10 to 30 wt %, based on the total weight of the quantum dot composition depending on the properties of the quantum dots.

[0049] Ligand In the quantum dot composition according to the present invention, the ligand serves to modify the surface of the quantum dots. Quantum dots have a barrier to dispersion in photopolymerizable monomers due to their hydrophobic surface characteristics, but the surface of the quantum dots can be modified with an appropriate ligand to improve the compatibility of the quantum dots with the photopolymerizable monomers.

[0050] According to one embodiment of the present invention, the ligand may include a primary ligand represented by the following Chemical Formula 1, and a secondary ligand having 3 to 40 carbon atoms and including a carboxyl group.

[0051] [ka]

[0052] In the above Chemical Formula 1, M is a divalent to tetravalent metal, m is an integer of 1 to 4, and X is independently an organic group having 3 to 20 carbon atoms; n is an integer from 2 to 4.

[0053] The primary ligand is a metal-thiol compound formed by reacting a metal salt with a thiol compound.

[0054] In the primary ligand, M is a metal having a valence of 2 to 4. For example, M is a metal of Groups 2 to 14, such as Mg, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Cd, In, or Sn. In Chemical Formula 1, n is determined by the valence of M and is an integer of 2 to 4.

[0055] In addition, in the above Chemical Formula 1, X is independently an organic group having 3 to 20 carbon atoms. For example, X is an ester (-C(=O)O-), an ether (-O-), a carbonyl (-C(=O)-), a carboxyl group (-C(=O)-OH), a sulfonyl (-SO 2 -), sulfide (-S-), sulfoxide (-SO-), alkoxy group (C n H 2n+1 X is an alkylene or alkenylene group having 3 to 20 carbon atoms and containing one or more functional groups selected from the group consisting of an ester (-C(=O)O-) and a hydroxyl group (-OH). Specifically, X is an organic group having 4 to 20 carbon atoms and containing an ester (-C(=O)O-) functional group.

[0056] In the primary ligand, the thiol group has excellent affinity with the surface of the quantum dot, and therefore can improve the dispersibility of the quantum dot in the photopolymerizable monomer. In addition, the primary ligand can include not only a thiol group but also an ester, ether, carbonyl, carboxyl group, alkoxy group, cycloalkoxy group, or hydroxyl group, thereby maximizing the dispersibility of the surface-modified quantum dot in the polar monomer having hydrophobicity. In addition, the quantum dot composition including such quantum dots can have advantageous properties (e.g., low viscosity) for display processes. Meanwhile, when a thiol-based compound having 3 or less carbon atoms is used, the surface of the quantum dots can be modified, but the high polarity of the surface-modified quantum dots makes it difficult to disperse them in general solvents and monomers.

[0057] The secondary ligand may have a carbon number of 3 to 40 and may include a carboxyl group. According to one embodiment of the present invention, the secondary ligand does not include a thiol group.

[0058] According to one embodiment of the present invention, the secondary ligand is represented by Formula 2:

[0059] [ka]

[0060] In the above Chemical Formula 2, L is a single bond or is selected from the group consisting of a substituted or unsubstituted C1-C20 alkylene group and a substituted or unsubstituted C1-C20 alkenylene group; A is a single bond or an ester (-C(=O)O-), ether (-O-), carbonyl (-C(=O)-), sulfonyl (-SO 2 a C1-C20 alkylene or alkenylene group containing one or more functional groups selected from the group consisting of aryl, aryloxy ... R is hydrogen or is selected from the group consisting of a substituted or unsubstituted C1-C20 alkyl group, and a substituted or unsubstituted C1-C20 alkenyl group.

[0061] Preferably, in the secondary ligand, A may include ester (-COO-), ether (-O-) and combinations thereof, and A is a C2-C15 alkylene or alkenylene group, preferably a C2-C10 alkylene or alkenylene group.

[0062] In general, thiol-based ligands are known to have high reactivity with the surface of quantum dots. However, quantum dot compositions containing only thiol-based ligands have problems such as harmful odor generation and increased viscosity, which reduces storage stability, making them unsuitable for use in inkjet compositions. The quantum dot composition according to the present invention exhibits low viscosity and excellent storage stability by using a primary ligand containing a thiol-based ligand together with a secondary ligand not containing a thiol group. In addition, the secondary ligand has excellent dispersibility in photopolymerizable monomers by containing functional groups such as ester (-C(=O)O-), ether (-O-), carbonyl (-C(=O)-), and carboxyl group (-C(=O)-OH). On the other hand, if the secondary ligand has 16 or more carbon atoms, problems may occur in which the surface of the quantum dots is not modified or dispersibility in general solvents and monomers is impaired.

[0063] According to one embodiment of the present invention, the molar ratio of the primary ligand to the secondary ligand is 1:30-20:1, preferably 1:15-10:1, and more preferably 1:8-5:1, but is not limited thereto.

[0064] According to one embodiment of the present invention, the mixing ratio of the quantum dots to the ligand is 1:1 to 20 by weight, preferably 1:1 to 10 by weight, and more preferably 1:5 to 10 by weight. Here, the ligand means the sum of the primary ligand and the secondary ligand.

[0065] Photopolymerizable Monomer In the quantum dot composition according to the present invention, the photopolymerizable monomer controls the overall crosslink density of the polymer matrix, which is the formulation in which the quantum dots (QDs) are dispersed, thereby expressing the structure and various physical properties of the matrix. It can also improve flexibility, and adhesion and adhesion to other materials.

[0066] The photopolymerizable monomer may include an aromatic monomer containing an aromatic ring such as a phenoxy group, a phenol group, or a phenyl group. For example, the aromatic monomer may be one selected from the group consisting of phenoxyethyl acrylate, phenoxyethyl methacrylate, ortho-phenylphenoxyethyl acrylate, phenoxybenzyl acrylate, benzyl acrylate, benzyl methacrylate, biphenyl methyl acrylate, bisphenol A diacrylate, bisphenol A dimethacrylate, bisphenol A ethoxylate, bisphenol A ethoxylate diacrylate, bisphenol A glycerolate diacrylate, bisphenol F ethoxylate diacrylate, or a combination thereof. The photopolymerizable monomer includes one or more of the aromatic monomers. The aromatic monomer has a refractive index of 1.50 or more, and can achieve the effect of improving light conversion efficiency by a high refractive effect.

[0067] In the present invention, the content of the aromatic monomer is 1 to 20% by weight, preferably 3 to 15% by weight, based on the total weight of the quantum dot composition, depending on the quantum dot.

[0068] The photopolymerizable monomer may include a (meth)acrylate monomer. For example, the (meth)acrylate monomer may include at least one of a (meth)acrylic group, a vinyl group, and an allyl group. Specifically, there are 1,6-hexanediol diacrylate, 1,6-cyclohexanediol diacrylate, 2,2-dimethyl-1,3-propanediol diacrylate, diethylene glycol diacrylate, dipropylene glycol diacrylate, 1,3-butylene glycol dimethacrylate, trimethylolpropane trimethacrylate, isobornyl acrylate, isobornyl methacrylate, tetrahydrofuryl acrylate, acryloylmorpholine, 2-phenoxyethyl acrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol mono(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, dipentaerythritol hexaacrylate, and dipentaerythritol hexamethacrylate. These may be used alone or in a mixture of two or more. In the present invention, 1,6-hexanediol diacrylate is preferred as the (meth)acrylate monomer in order to achieve the viscosity characteristics of the quantum dot composition.

[0069] In the present invention, the content of the photopolymerizable monomer is 1 to 60% by weight, preferably 3 to 50% by weight, based on the total weight of the quantum dot composition, depending on the quantum dot.

[0070] Photoinitiators In the quantum dot composition according to the present invention, the photoinitiator is a component that is excited by a light source such as ultraviolet (UV) light to initiate photopolymerization, and any photopolymerization initiator commonly used in the art can be used without limitation. Examples of such compounds include acetophenone-based compounds, benzophenone-based compounds, thioxanthone-based compounds, benzoin-based compounds, triazine-based compounds, and oxime-based compounds.

[0071] Non-limiting examples of photoinitiators that can be used include ethyl (2,4,6-trimethylbenzoyl)phenylphosphinate, Irgacure 184, Irgacure 369, Irgacure 651, Irgacure 819, Irgacure 907, benzion alkyl ether, benzophenone, benzyl dimethyl acetone, hydroxycyclohexyl phenyl acetone, chloroacetophenone, 1,1-dichloroacetophenone, diethoxyacetophenone, hydroxyacetophenone, 2-chlorothioxanthone, 2-ethylanthraquinone (2-ETAQ), 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, methyl benzoylformate, etc. These may be used alone or in combination of two or more.

[0072] The content of the photoinitiator may be appropriately adjusted within a range known in the art. For example, it is 0.01 to 10 wt %, preferably 0.1 to 5 wt %, based on the total weight of the quantum dot composition. When the content of the photoinitiator falls within the above range, the photopolymerization reaction can be sufficiently carried out without deteriorating the physical properties of the matrix.

[0073] Diffusion Agent In the quantum dot composition according to the present invention, the diffusing agent reflects light that is not absorbed by the light conversion material and allows the light conversion material to absorb the reflected light again, i.e., the diffusing agent increases the amount of light absorbed by the light conversion material, thereby increasing the light conversion efficiency.

[0074] The diffusing agent may be any diffusing agent component known in the art without any restrictions. Such a diffusing agent may be a solid diffusing agent powder or a dispersion liquid in which the diffusing agent is dispersed.

[0075] A non-limiting example of a diffusing agent that can be used is barium sulfate (BaSO 4), calcium carbonate (CaCO 3 ), titanium dioxide (TiO 2 ), zirconia (ZrO 2 ) or a combination thereof. The average particle size and shape of the diffusing agent are not particularly limited and may be appropriately selected from among those known in the art. As an example, the average particle size (D50) is 150 nm to 250 nm, specifically, 180 nm to 230 nm. When the average particle size of the diffusing agent is within the above range, a more excellent light diffusing effect can be obtained, and the light conversion efficiency can be increased.

[0076] The content of the diffusing agent may be appropriately adjusted within a range known in the art. For example, it is 0.01 to 10 wt % based on the total weight of the quantum dot composition, and preferably 0.1 to 5 wt %. When the content of the diffusing agent falls within the above range, it can exhibit an effect of improving the light conversion efficiency without deteriorating the physical properties of the matrix.

[0077] Polymerization Inhibitor In the quantum dot composition according to the present invention, the polymerization inhibitor is a substance that reacts with radicals to form low-reactivity radicals or compounds that do not cause a polymerization reaction, and can control the rate of the photopolymerization reaction.

[0078] The polymerization inhibitor may be any known substance in the art without limitation, for example, a quinone compound, a phenol or aniline compound, or an aromatic nitro or nitroso compound. Specifically, there are hydroquinone (HQ), methylhydroquinone (THQ), hydroquinone monomethyl ether (MEHQ), hydroquinone monoethyl ether (EEHQ), 1,4-benzoquinone (BQ), 2,5-diphenylbenzoquinone (DPBQ), methyl-1,4-benzoquinone (MBQ), phenyl-1,4-benzoquinone (PBQ); 2,6-di-tert-butyl-4-methylphenol (BHT), 2,6-diphenyl-4-octadecyloxyphenol, catechol; phenothiazine, bis(α-methylbenzyl)phenothiazine, 3,7-dioctylphenothiazine, bis(α,α-dimethylbenzyl)phenothiazine; dimethyldithiocarbamic acid, diethyldithiocarbamic acid, dipropyldithiocarbamic acid, dibutyldithiocarbamic acid, diphenyldithiocarbamic acid, etc. These may be used alone or in combination of two or more.

[0079] The content of the polymerization inhibitor can be appropriately adjusted within a range known in the art, for example, 0.01 to 2% by weight, preferably 0.05 to 1 part by weight, based on the total weight of the quantum dot composition.

[0080] Other additives In addition to the above-mentioned components, the quantum dot composition of the present invention may contain additives known in the art without limitation, as long as the additives do not impair the effects of the present invention. In this case, the content of the additives may be appropriately adjusted within the range known in the art.

[0081] Examples of usable additives include silane compounds, siloxane compounds, antioxidants, polymerization inhibitors, lubricants, surface conditioners, surfactants, adhesion promoters, defoamers, slip agents, solvents, wetting agents, light stabilizers, stain inhibitors, softeners, thickeners, polymers, etc. These may be used alone or in combination of two or more.

[0082] The silane-based compound serves to impart adhesiveness to the matrix, and the siloxane-based compound serves to impart wetting properties. Such silane-based compounds and siloxane-based compounds may be any compounds known in the art without limitation.

[0083] The antioxidant suppresses discoloration caused by heat or light exposure, and by various oxidizing gases such as ozone, active oxygen, NOx, and SOx (X is an integer), and in the present invention, the addition of the antioxidant can prevent coloring of the matrix and reduce a decrease in film thickness caused by decomposition. Examples of usable antioxidants include hydrazides, hindered amine antioxidants, nitrogen-containing heterocyclic mercapto compounds, thioether antioxidants, hindered phenol antioxidants, ascorbic acids, zinc sulfate, thiocyanates, thiourea derivatives, sugars, nitrites, sulfites, thiosulfates, and hydroxylamine derivatives.

[0084] The leveling agent may be included for the purpose of increasing the adhesive strength within the composition by leveling the quantum dot composition so that the composition is coated evenly and smoothly. The leveling agent may include an acrylic or silicone-based agent alone or in combination of two or more types. As an example, the leveling agent may include polyether-modified polydimethylsiloxane, and may include a (meth)acryloyl group added to the polyether chain.

[0085] A surfactant may be included for the purpose of mixing and coating uniformity of the quantum dot composition. The surfactant may be a typical cationic, anionic, zwitterionic, or nonionic surfactant known in the art, and may be, for example, one or more of a fluorosurfactant, a silicone surfactant, and a fluorosilicone surfactant.

[0086] The light stabilizer is an ultraviolet absorbing agent and has the effect of increasing the weather resistance of the matrix, while the softening agent is for mitigating the occurrence of cracks in the dried polymer matrix, and can improve the impact resistance and flex resistance by mitigating the occurrence of cracks in the cured matrix.

[0087] <Method of manufacturing quantum dot composition> In another embodiment of the present invention, a method for producing a quantum dot composition includes modifying the surface of quantum dots, dispersing the quantum dots in a photopolymerizable monomer to obtain a quantum dot dispersion, and further adding an oligomer and a photopolymerizable monomer to the quantum dot dispersion. The further added photopolymerizable monomer includes one or more aromatic monomers having an aromatic ring such as a phenoxy group, a phenol group, or a phenyl group.

[0088] The oligomer may include a compound containing a carbon-carbon double bond and a compound containing a thiol group, and may be prepared as an oligomer through a polymerization reaction after stirring at room temperature before being mixed with the quantum dot dispersion. The oligomer may further include a thermal initiator and a polymerization inhibitor.

[0089] Modifying the surface of the quantum dot may include performing a primary surface modification by adding a primary ligand represented by the following chemical formula 1, and then performing a secondary surface modification by adding a secondary ligand having 3 to 40 carbon atoms and including a carboxyl group.

[0090] [ka]

[0091] In the above Chemical Formula 1, M is a divalent to tetravalent metal; m is an integer of 1 to 4, and X is independently an organic group having 3 to 20 carbon atoms; n is an integer from 2 to 4.

[0092] Specifically, quantum dots are synthesized, a primary ligand is added to the solution in which the quantum dots are synthesized to perform primary surface modification, and the solution is then centrifuged to obtain quantum dots with primary surface modification. The quantum dots with primary surface modification are then dispersed in a photopolymerizable monomer, and a secondary ligand having 3 to 40 carbon atoms and including a carboxyl group is then added to perform secondary surface modification of the quantum dots.

[0093] Here, the quantum dots can be produced by any method known in the art (eg, a high-temperature injection method, a method using a microfluidic reactor, a microwave irradiation method, etc.).

[0094] The quantum dots can be synthesized by adding a primary ligand to a solution in which the quantum dots are synthesized while maintaining the temperature at about 60°C, stirring and reacting for 30 minutes to 3 hours to primarily modify the surface of the quantum dots, and then adding a secondary ligand and stirring and reacting for 30 minutes to 3 hours to secondary modify the surface of the quantum dots.

[0095] The surface modification of the quantum dots can be carried out in two stages to prevent the formation of an addition product due to the reaction between the primary ligand and the secondary ligand. Meanwhile, when the primary ligand and the secondary ligand are simultaneously added to the quantum dots, an addition product can be formed by a thiol-ene reaction between the thiol group of the primary ligand and the acrylate of the secondary ligand. Such an addition product can increase the viscosity of the quantum dot composition when the surface-modified quantum dots are dispersed in a photopolymerizable monomer.

[0096] After the surface of the quantum dots is modified by the above method, the surface-modified quantum dots are obtained by centrifugation, and the quantum dot dispersion liquid can be prepared by dispersing the surface-modified quantum dots obtained in a photopolymerizable monomer.

[0097] Then, a photopolymerizable monomer is further added to the prepared quantum dot dispersion and oligomer, and a polymerization inhibitor, a photoinitiator, and a diffusing agent are added and mixed to prepare a quantum dot composition. Here, the photopolymerizable monomer further added includes one or more aromatic monomers having an aromatic ring such as a phenoxy group, a phenol group, or a phenyl group, and the content of the aromatic monomer is 1 to 20 wt%, preferably 3 to 15 wt%, based on the total weight of the quantum dot composition depending on the quantum dot.

[0098] The other photopolymerizable monomers are as described above in the quantum dot composition to the extent that they overlap.

[0099] <Cured product, light-emitting element, and display device> The present invention can provide a cured product containing the quantum dot composition. The cured product according to the present invention has excellent optical properties, specifically, a light absorptance of 80% or more. In addition, the cured product has a light conversion rate of 35% or more.

[0100] The cured product may be prepared by applying the quantum dot composition onto a substrate by a spin coating method to form a pattern, and curing the pattern.

[0101] The present invention provides a light-emitting device comprising the quantum dot composition. For example, a color filter is a thin-film optical component that extracts three colors, red, green, and blue, from white light emitted from a backlight source on a pixel-by-pixel basis to realize colors on a liquid crystal display.

[0102] Such color filters are manufactured by methods such as dyeing, pigment dispersion, printing, and electrodeposition. Also, color filters containing quantum dot compositions are manufactured by inkjet printing. In the inkjet printing, materials are used only for desired pixels, so that waste of unnecessary materials can be prevented.

[0103] The present invention also provides a display device including the quantum dot composition, which may be, but is not limited to, a liquid crystal display (LCD), an electroluminescent display (EL), a plasma display panel (PDP), a field emission display (FED), an organic light emitting device (OLED), and the like.

[0104] The present invention will be described in more detail with reference to the following examples. However, the following examples are for illustrative purposes only and are not intended to limit the scope of the present invention.

[0105] [Production Example 1] Production of primary ligand 1) Approximately 280 g of poly(ethylene glycol) methyl ether 400 and approximately 50 g of mercaptosuccinic acid are added, and the mixture is heated to approximately 100° C. and reacted for approximately 12 hours. After the reaction is complete, the mixture is cooled to room temperature to obtain 330 g of bis-(methoxypolyethylene glycol) mercaptosuccinate-400. 2) In a round-bottom flask, add zinc chloride (ZnCl 2 1.7 g of Zn-bis-(methoxypolyethylene glycol)mercaptosuccinate-400) and 32 g of bis-(methoxypolyethylene glycol)mercaptosuccinate-400 were added to 134.5 g of hexyl acetate and dissolved by stirring at about 60° C. Then, HCl was removed under vacuum for 2 hours to produce the primary ligand Zn-bis-(methoxypolyethylene glycol)mercaptosuccinate-400.

[0106] [Production Example 2] Production of secondary ligand The compound represented by the chemical formula B-1 was added to hexyl acetate in a round-bottom flask and stirred at room temperature for about 1 hour to prepare secondary ligand mono(2-acryloyloxyethyl)succinate. [ka]

[0107] [Production Example 3] Production of quantum dot (QD) dispersion 1) 750 ml of InZnP / ZnSe / ZnS (core / shell / shell) quantum dot dispersion solution (Hansol, quantum dot solid powder 20 wt%; hexyl acetate) was heated to about 60°C in a nitrogen atmosphere and stirred. About 9 g of the prepared primary ligand, Zn-bis-(methoxypolyethylene glycol) mercaptosuccinate-400, was added and stirred for about 2 hours to perform primary surface modification of the quantum dots. 2) About 30 g of the secondary ligand mono(2-acryloyloxyethyl)succinate was added to the solution containing the quantum dots that had been primarily surface-modified, and the solution was stirred for about 2 hours to perform secondary surface modification of the quantum dots. 3) The solution containing the quantum dots after the surface modification was centrifuged twice with cyclohexane to obtain quantum dot powder, which was then dispersed in 1,6-hexanediol diacrylate (manufactured by MIWON) at 60 wt% to produce a QD dispersion.

[0108] [Production Example 4] Production of Oligomer A Based on 100 parts by weight of triallyl isocyanurate, 1 part by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) and 0.1 parts by weight of methylhydroquinone were dissolved to prepare crude liquid A. 42.9 parts by weight of crude liquid A, 28.6 parts by weight of phenol acrylate, and 28.6 parts by weight of glycol di(3-mercaptopropionate) were mixed and stirred at room temperature for 1 hour. After stirring, the reactor temperature was set to about 80°C, and oligomer A was produced by oligomer polymerization reaction.

[0109] <Example 1-1> Preparation of quantum dot composition A quantum dot composition was prepared by mixing 70 parts by weight of the green quantum dot dispersion (Hansol, quantum dot polymer 60 wt%: 1,6-hexanediol diacrylate 40 wt%) that had been surface-modified and 14.5 parts by weight of oligomer A, followed by mixing 5.4 parts by weight of 1,6-hexanediol diacrylate (manufactured by MIWON), 3 parts by weight of phenoxyethyl acrylate (manufactured by Green Chemicals), 0.1 parts by weight of methylhydroquinone, 2 parts by weight of ethyl (2,4,6-trimethylbenzoyl) phenylphosphinate as a photoinitiator, and 5 parts by weight of titanium dioxide as a diffusing agent.

[0110] <Example 1-2> The same preparation method as in Example 1-1 was used, except that 12.5 parts by weight of Oligomer A and 5 parts by weight of phenoxyethyl acrylate were mixed.

[0111] <Example 1-3> The same method as in Example 1-1 was used to prepare the resin, except that 10.5 parts by weight of Oligomer A and 7 parts by weight of phenoxyethyl acrylate were mixed.

[0112] <Example 1-4> The same method as in Example 1-1 was used to prepare the resin composition, except that 3 parts by weight of bisphenol A diacrylate was used instead of 3 parts by weight of phenoxyethyl acrylate.

[0113] <Example 1-5> The same method as in Example 1-2 was used to prepare the resin composition, except that 5 parts by weight of bisphenol A diacrylate was used instead of 5 parts by weight of phenoxyethyl acrylate.

[0114] <Comparative Example 1-1> The same method as in Example 1-1 was used to prepare the resin, except that 17.5 parts by weight of Oligomer A was mixed instead of 14.5 parts by weight of Oligomer A and 3 parts by weight of phenoxyethyl acrylate.

[0115] <Comparative Example 1-2> The same preparation method as in Comparative Example 1-1 was used, except that 10.5 parts by weight of Oligomer A and 12.4 parts by weight of 1,6-hexanediol diacrylate were used.

[0116] <Comparative Example 1-3> The same preparation method as in Comparative Example 1-1 was used, except that 22.9 parts by weight of 1,6-hexanediol diacrylate was mixed in place of 17.5 parts by weight of Oligomer A.

[0117] <Example 2-1> After the surface modification was completed, 46.5 parts by weight of the red quantum dot dispersion (Hansol, quantum dot polymer 60 wt%: 1,6-hexanediol diacrylate 40 wt%) and 35.5 parts by weight of Oligomer A were mixed, and then 5.9 parts by weight of 1,6-hexanediol diacrylate, 5 parts by weight of bisphenol A diacrylate, 0.1 parts by weight of methylhydroquinone, 2 parts by weight of ethyl (2,4,6-trimethylbenzoyl) phenylphosphinate as a photoinitiator, and 5 parts by weight of titanium dioxide as a light scattering agent were mixed to prepare a quantum dot composition.

[0118] <Comparative Example 2-1> The same method as in Example 2-1 was used to prepare the resin composition, except that 10.9 parts by weight of 1,6-hexanediol diacrylate was mixed instead of 5.9 parts by weight of 1,6-hexanediol diacrylate and 5 parts by weight of bisphenol A diacrylate.

[0119] <Comparative Example 2-2> The same method as in Comparative Example 2-1 was used to prepare the resin, except that 35.5 parts by weight of Oligomer A and 46.4 parts by weight of 1,6-hexanediol diacrylate were mixed instead of 10.9 parts by weight of Bisphenol A diacrylate.

[0120] The compositions of the examples and comparative examples are summarized in Table 1 below.

[0121] [Table 1]

[0122] <Experimental Example 1. Evaluation of light conversion rate and light absorption rate of quantum dot cured material> 1) The green quantum dot compositions of Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-3 were applied to a thickness of 10 μm on a 2 cm × 2 cm glass substrate using a spin coater (Mikasa, Opticoat MS-A150), and then cured at 4000 mJ / cm using an LED curing device with a wavelength of 395 nm. 2 A cured film was produced by irradiating the sample with a 2 cm x 2 cm single film specimen. Then, a 2 cm x 2 cm single film specimen was loaded into an integrating sphere device (QE-2100, manufactured by Otsuka Electronics Co., Ltd.) to measure the initial light absorption rate and the light conversion rate after curing (QE). Then, the sample was heat-treated (post-baked) at 180°C for 30 minutes in a nitrogen atmosphere, and the light conversion rate (QE) was measured. The results are shown in Table 2 below.

[0123] [Table 2]

[0124] The cured films produced in Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-3 were produced with a substantially uniform thickness in the range of 10 μm to about 0.3 μm.

[0125] It was confirmed that the optical absorptance of all the examples was 85% or more, and the optical conversion rate was 34% or more, showing excellent optical properties.

[0126] In particular, in Examples 1-1 to 1-3, as the content of phenoxyethyl acrylate increased, the light conversion rate increased from 34.3% to 35.0%, and in Examples 1-4 to 1-5, as the content of bisphenol A diacrylate increased, the light conversion rate increased from 35.0% to 35.3%. On the other hand, in Comparative Examples 1-1 to 1-3, which do not contain an aromatic monomer having an aromatic ring such as a phenoxy group, a phenol group, or a phenyl group, the light absorptance is 85% or more, but the light conversion rate is somewhat low, from 31.8% to 33.8%.

[0127] Therefore, the excellent optical characteristics of Examples 1-1 to 1-5 are well maintained both before and after heat treatment, and thus the light-emitting devices or display devices employing Examples 1-1 to 1-5 can maintain their excellent optical characteristics for a longer period of time than the light-emitting devices or display devices employing Comparative Examples 1-1 to 1-3.

[0128] 2) Using the red quantum dot compositions prepared in Example 2-1 and Comparative Examples 2-1 and 2-2, cured films were prepared in the same manner as above, and the light absorptivity and light conversion rate were measured. In addition, the light conversion rate after heat treatment was measured in the same manner as above. The results are shown in Table 3 below.

[0129] [Table 3]

[0130] The light absorption rates all showed values ​​of approximately 88 to 89%, with Example 2-1 showing a light conversion rate of 41.4%, while Comparative Example 2-1, which did not contain the aromatic monomer bisphenol A diacrylate, showed a slightly lower light conversion rate of 40.1%, and Comparative Example 2-2, in which neither bisphenol A diacrylate nor oligomer was applied, showed a somewhat lower light conversion rate of 36.6%.

[0131] Therefore, since the excellent optical characteristics of Example 2-1 are well maintained both before and after heat treatment, the light emitting device or display device to which Example 2-1 is applied can maintain the excellent optical characteristics for a longer period of time than the light emitting device or display device to which Comparative Examples 2-1 to 2-2 are applied.

[0132] <Experimental Example 2. Viscosity evaluation of quantum dot composition> The viscosity of the green quantum dot compositions according to Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-3 was measured using a rotational rheometer (HAAKE MARS manufactured by Thermo Scientific) at room temperature (25° C.).

[0133] The viscosity of the red quantum dot compositions according to Example 2-1 and Comparative Examples 2-1 and 2-2 was also measured by the same method. The results are shown in Table 4 below.

[0134] [Table 4]

[0135] The green quantum dot composition examples have viscosities of about 151 cps and 289 cps, and the red quantum dot composition example has a viscosity of about 582 cps, which confirms that the compositions have viscosities suitable for EHD inkjet printing as well as inkjet printing.

[0136] On the other hand, Comparative Examples 1-3 and 2-2, which do not contain an aromatic monomer, exhibit low viscosities of about 35 cps and 26 cps, and it can be confirmed that they are not suitable for EHD inkjet printing.

[0137] In addition, in the case of Comparative Examples 1-1 and 2-1 in which oligomers were used, although they were suitable in terms of viscosity, it is considered that they are difficult to apply in practice when the results of Experimental Examples 1 and 2 are taken into consideration.

[0138] <Experimental Example 3. EHD (electrohydrodynamic) inkjet printing (inkjetting properties) evaluation> The inkjetting properties (ejection properties) of the green quantum dot compositions according to Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-3 were measured. Specifically, the EHD inkjetting properties were evaluated using an iEHD printer (manufactured by ENJET) with a nozzle inner diameter of 75 μm.

[0139] In addition, the inkjetting properties of the red quantum dot compositions according to Examples 2-1 to 2-2 and Comparative Example 2-1 were measured by the same method, and the results are shown in Table 5 below.

[0140] [Table 5]

[0141] It was confirmed that the green quantum dot composition examples all showed no nozzle clogging and good EHD inkjet printing at 1.5 kV delta voltage, -0.5 kV to -2.0 kV, and the red quantum dot composition examples also showed no nozzle clogging and good EHD inkjet printing at 2.2 kV delta voltage, -0.6 kV to -2.8 kV.

[0142] On the other hand, in Comparative Examples 1-2, 1-3, and 2-2, which had a viscosity of 100 cps or less, a problem was found in that the low viscosity meant that the ink was not properly jetted only to the desired area during EHD printing.

[0143] It will be obvious to those having ordinary skill in the art to which the present invention pertains that the present invention is not limited to the above-described embodiments and can be modified or altered in various ways without departing from the technical scope of the present invention.

Claims

1. Quantum dots, photopolymerizable monomers and oligomers, The quantum dot composition, wherein the photopolymerizable monomer comprises a compound containing an aromatic ring.

2. 2. The quantum dot composition of claim 1, wherein the compound containing an aromatic ring comprises a phenoxy group, a phenol group, or a phenyl group.

3. 2. The quantum dot composition of claim 1, wherein the compound containing an aromatic ring is phenoxyethyl acrylate, phenoxyethyl methacrylate, ortho-phenylphenoxyethyl acrylate, phenoxybenzyl acrylate, benzyl acrylate, benzyl methacrylate, biphenyl methyl acrylate, bisphenol A diacrylate, bisphenol A dimethacrylate, bisphenol A ethoxylate, bisphenol A ethoxylate diacrylate, bisphenol A glycerolate diacrylate, or bisphenol F ethoxylate diacrylate.

4. The quantum dot composition of claim 1 , wherein the photopolymerizable monomer further comprises an acrylate monomer.

5. The quantum dot composition of claim 1 , wherein the oligomer comprises a compound containing a carbon-carbon double bond and a compound containing a thiol group.

6. The quantum dot composition according to claim 5, wherein the compound containing a carbon-carbon double bond includes one or more compounds containing a phenol group.

7. The quantum dots include a primary ligand represented by the following formula 1: The quantum dot composition of claim 1, which is surface-modified with a secondary ligand having 3 to 40 carbon atoms and including a carboxyl group: 【Chemistry 1】 In the above Chemical Formula 1, M is a divalent to tetravalent metal; m is an integer of 1 to 4, and X is independently an organic group having 3 to 20 carbon atoms; n is an integer from 2 to 4.

8. The quantum dot composition according to claim 1, having a viscosity in the range of 150 to 600 cps at room temperature.

9. 10. The quantum dot composition of claim 1, for use in electrohydrodynamic inkjet printing.

10. After modifying the surface of the quantum dots, they are dispersed in a photopolymerizable monomer to obtain a quantum dot dispersion liquid; The quantum dot dispersion liquid further contains an oligomer and a photopolymerizable monomer. The method for producing a quantum dot composition further comprises adding a photopolymerizable monomer containing a compound having an aromatic ring.

11. The method for producing a quantum dot composition according to claim 10, wherein the compound containing an aromatic ring contains a phenoxy group, a phenol group, or a phenyl group.

12. The compound containing an aromatic ring is phenoxyethyl acrylate, phenoxyethyl methacrylate, ortho-phenylphenoxyethyl acrylate, phenoxybenzyl acrylate, benzyl acrylate, benzyl methacrylate, biphenyl methyl acrylate, bisphenol A diacrylate, bisphenol A dimethacrylate, bisphenol A ethoxylate, bisphenol A ethoxylate diacrylate, bisphenol A glycerolate diacrylate, or bisphenol F ethoxylate diacrylate. The method for producing a quantum dot composition according to claim 10.

13. The method for producing a quantum dot composition according to claim 10 , wherein the photopolymerizable monomer further comprises an acrylate monomer.

14. The method for producing a quantum dot composition according to claim 10, wherein the surface modification of the quantum dots includes a primary surface modification by adding a primary ligand represented by the following chemical formula 1, and then a secondary surface modification by adding a secondary ligand having 3 to 40 carbon atoms and including a carboxyl group: 【Chemistry 2】 In the above Chemical Formula 1, M is a divalent to tetravalent metal; m is an integer of 1 to 4, and X is independently an organic group having 3 to 20 carbon atoms; n is an integer from 2 to 4.

15. The method for producing a quantum dot composition according to claim 10, wherein the oligomer is produced by mixing a compound containing a carbon-carbon double bond and a compound containing a thiol group.

16. The method for producing a quantum dot composition according to claim 15, wherein the compound containing a carbon-carbon double bond includes one or more compounds containing a phenol group.

17. The oligomer further comprises a thermal initiator and a polymerization inhibitor; The method for producing a quantum dot composition according to claim 15, wherein the oligomer is prepared as an oligomer through a polymerization reaction after being stirred at room temperature before being mixed with the quantum dot dispersion.

18. A cured film produced using the quantum dot composition of claim 1.

19. A light-emitting device comprising the quantum dot composition of claim 1.

20. A display device comprising the light emitting element of claim 19.

Citation Information

Patent Citations

  • Matrix for quantum dot articles

    JP2018538557A

  • Wavelength conversion member, backlight unit, image display device, and method of manufacturing wavelength conversion member

    JP2019174561A

  • Composition having light-emitting properties, and use therefor

    JP2020076035A

  • Metal halide perovskite light emitting device and method for manufacturing same

    US20220194969A1

  • Dosage regimen for the treatment of cancer

    WO2021214253A1